Futbol ekonomisi: 2 ülke kıyaslaması (İngiltere-Türkiye) - Aydın, Elif (My University, 2008)
Son yıllarda futbol sadece insanları eglendiren bir spor dalı olmaktan çıkmıstır ve ekonomik boyutu milyar dolarlara ulasan uluslararası bir endüstri haline gelmistir. Ülkelerin futbol ekonomilerinin gelismesinde, ülkelerin futbol federasyonlarının etkin yönetimlerinin yanı sıra, ülkelerin genel ekonomilerinin gelismis olmasının ve futbol taraftarlarının desteginin de önemi büyük olmustur. Bu çalısmada, ngiltere ve Türkiye futbol ekonomisi ele alınmıs ve bu baglamda ngiliz Premier Lig ile Türkiye Turkcell Süper Lig’in tarihçesi, rekabetçi yapısı, gelir kalemleri ve sahip oldugu ekonomik degeri hakkında kıyaslama yapılmıstır. Kıyaslama sonucunda ngiliz Premier Lig’in Avrupa’nın en degerli futbol liglerinden biri ve Turkcell Süper Lig’e göre daha üstün bir futbol ekonomisi oldugu görülmüstür.

FOOTBALL ECONOMCS: COMPARISON OF TWO COUNTRIES (ENGLAND AND TURKEY) For the latest years, football is no longer an enjoyable sport, it has been an international industry worthed more than millon dollars. Besides the effective management strategies of football associations, development of countrys’ general economies and supporting of football fans have been important points on development of countrys’ football economies. With this study football ecomies of Turkey and England are explained. Under this subject, the histories, competitive structres, income sources and economic values of English Premier League and Turkish Turkcell Super League has been compared. For a result, Premier League has been mentioned as one of the most valued football league in the European Football Leagues and a bigger football economy than Turkcell Super League.
Keywords: İngiltere_Futbol_Türkiye; Spor_Ekonomi_İngiltere; Spor_Ekonomi_Türkiye